Philosophical Translation Analysis of Jeremy Munday’s Introducing Translation Studies - Arrosyid, Rofingudin; Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to investigate the philosophical theory contained in Jeremy Munday's book. The data from this study were obtained from Jeremy Munday's book Introducing Translation Studies: Theories and Applications, published by Routledge, London, 2001. Literature study research method was used by reviewing the philosophy of translation theory from Jeremy Munday's book. After getting the relevant surveyors, the researchers identified the translation philosophy theory contained in the book. From the results of the book's investigations, it was known that some experts were trying to introduce the philosophical theory of modern translation. In contrast, the experts and their fields of study were George Steniner, who researched on the theory of interpretation of meaning, Ezra Pound, who researched on the power of language, Walter Benjamin was about the purity of the translator's task, and Derrida who researched about the relationship between deconstruction translation (text reading method). In addition, there are also several case studies related to the application of the philosophical theory of language strategies put forward by these experts. All of these translation theories discussed the principles of translation and their relation to improving translation studies.